How student beliefs related to mathematics are influenced by students' past experiences - Hakim, Arif Rahman; Dewi, Mutia Lina; Zamrudy, Windi; Dewajani, Heny; Ro'isatin, Anis (Technium Social Sciences Journal, 2023)
The importance of belief in learning mathematics has now been widely recognized. Some researchers point out that success in learning mathematics, particularly in problem solving, is influenced by students' beliefs related to mathematics and their self-perception as mathematics learners. The aim of this study is to investigate the connection between prior experience and student beliefs related to mathematics. The study uses a qualitative method, conducted through the use of a questionnaire, a mathematics test, and interviews. A questionnaire was randomly distributed to the students of the State Polytechnic of Malang attending mathematics lessons in the 2021/2022 academic year; 46 students, consisting of 32 males and 14 females, filled it out. An interview was conducted with seven randomly selected students out of the 46 who had filled out questionnaires. The results showed that met-before students’ Polytechnic influenced belief about: (1) understanding mathematics; (2) learning mathematics; (3) steps and time in solving mathematics problem; (4) teaching mathematics; (5) self; and (6) usefullness mathematics.